ANALISIS PENGARUH KOMUNIKASI, LINGKUNGAN KERJA, MOTIVASI, DAN ETOS KERJA TERHADAP KINERJA KARYAWAN KLINIK PRATAMA BENING’S MANADO - Lumowa, Rollin Prassetyo; Lengkong, Victor P. K; Lumanauw, Bode (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2025)
This study aims to examine the influence of communication, work environment, motivation, and work ethic on employee performance at the Pratama Bening's Clinic in Manado. This study used a quantitative method with a causal associative approach. Data collection was conducted by distributing questionnaires to the entire population of 29 employees, so the sampling technique used a saturated sampling method (census). The results of the validity and reliability tests showed that all instrument items met the measurement criteria, and the classical assumption tests (normality, multicollinearity, and heteroscedasticity) were met so that the model was feasible to be analyzed using multiple linear regression. The results showed that communication, work environment, motivation, and work ethic simultaneously had a significant effect on employee performance. Partially, communication and work environment were proven to have a positive and significant effect on performance, while motivation and work ethic had a positive but insignificant effect. These findings indicate that increasing communication effectiveness and improving physical conditions are the dominant factors driving performance. Managerial implications suggest the need to strengthen two-way communication, provide adequate work facilities, and re-evaluate the incentive system and work discipline so that motivation and work ethic can contribute more optimally to performance achievement.